Refining the Global Goal on Adaptation indicators through farmer perspectives - Eastern Africa Farmers Federation (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
This briefing note, developed by the Eastern Africa Farmers Federation (EAFF) Secretariat and its member organisations, presents key observations and recommendations to refine the Global Goal on Adaptation (GGA) indicators from a farmer perspective. It aims to inform and influence climate negotiations, ensuring that farmer priorities are adequately reflected in global adaptation frameworks. The brief was developed following a workshop co-hosted by EAFF, the Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA), and the Adaptation Insights project in Nairobi, Kenya, on 10 June 2025.